Import shock and local labour market outcomes: A Sino-Indian case study - Feiyang Shi (Graduate Institute of International and Development Studies, 2022)
Focusing on Sino-Indian trade, this paper uses detailed district-level data, exploits India's drastic increase in imports from China since 2001, and uses the instrumental variables approach to examine the impact of trade shock on the local labour market outcomes. Through a matching procedure, the geographical coverage of the paper is significantly improved comparing with prior studies. The range of labour market outcome variables examined is also much wider, including wage, residual wage fluctuation, and employment and underemployment as shares of working-age population. By exploiting spatial variations in industrial activities and labour participation in the industries, the paper finds that, unlike in some other cases, the import competition from China did not have a significant impact on the Indian district average wages. However, it did result in an increase in employment share. In further contribution, the paper also allows heterogeneous effects across consumption, age, gender, occupation and industrial groups. The results confirm that the effect of import shock is not uniformly distributed within the districts. Rather, it varies with respect to certain socio-economic characteristics.
Keywords: F14; F16; J16; 330; International Trade; Wages; Income Inequality; Import shock; Underemployment